A Reminder System for Postpartum DM Screening in GDM Patients: A Randomized Controlled Trial (RCT) [20Q]. (May 2017) - Khalifeh, Adeeb; Iyer, Jayasree; Cantor, Eva; Quist-Nelson, Johanna; Tumas, Jordyn; Berghella, Vincenzo
Abstract : INTRODUCTION: The postpartum period is an opportunity to screen for diabetes mellitus (DM) in pregnancies complicated by gestational diabetes mellitus (GDM). We evaluated whether a reminder system increases DM screening in the postpartum period. METHODS: This was a multicenter RCT of women who had pregnancies complicated by GDM and whom we anticipated would undergo postpartum screening for DM. Our intervention was a reminder system comprising of providing the patient with a screening test laboratory requisition prior to discharge from the hospital and of a phone reminder 6 weeks postpartum. Our control group included patients undergoing routine DM screening during their 6 week postpartum visits. The primary outcome was DM screening uptake in the postpartum period. Data was analyzed using Chi squared and Fisher exact tests. RESULTS: A total of 75 patients were randomized. 38 were assigned to the reminder system and 37 to the control group. Maternal age, race, insurance and parity were similar between both groups. From the intervention group, 31.6% (n=12) performed postpartum DM screening compared to 24.1% (n=10) in the control group (p=0.1). This increase was significant in patients with public insurance (p=0.04) but not in patients with private insurance (p=0.19). 31.8% (7/22) of patients who completed the screening test were diagnosed with prediabetes but none with DM. CONCLUSION: A reminder system for postpartum DM screening in GDM patients did not increase testing uptake. However, a reminder system may be beneficial in patients with lower socioeconomic status.